2021
DOI: 10.1093/europace/euab171
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the physical performance in children with asymptomatic pre-excitation

Abstract: Aims Pre-excitation syndrome can lead to recurrent supraventricular tachycardias (SVTs) and carries a risk of sudden cardiac death (SCD). However, an underestimated consequence of antegrade conduction through an accessory pathway is fusion of intrinsic and accessory conduction that causes asynchronous activation and myocardial contraction that could be a cause for cardiac dysfunction and dilation. It is not known to what extent pre-excitation affects myocardial and physical performance in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Cases of improvement of exercise intolerance after RFCA in patients with ventricular pre-excitation have also been reported (27)(28)(29). Using cardiopulmonary exercise testing, Książczyk et al (30) demonstrated impaired physical performance in asymptomatic children with ventricular preexcitation compared to matched healthy children (VO 2 max: 36.67±6.66 vs. 44.45±8.37 mL/kg/min; P<0.001). Their follow-up study identified improvement in the physical performance in children with ventricular pre-excitation (31).…”
Section: Exercise Intolerance In Patients With Ventricular Preexcitationmentioning
confidence: 94%
“…Cases of improvement of exercise intolerance after RFCA in patients with ventricular pre-excitation have also been reported (27)(28)(29). Using cardiopulmonary exercise testing, Książczyk et al (30) demonstrated impaired physical performance in asymptomatic children with ventricular preexcitation compared to matched healthy children (VO 2 max: 36.67±6.66 vs. 44.45±8.37 mL/kg/min; P<0.001). Their follow-up study identified improvement in the physical performance in children with ventricular pre-excitation (31).…”
Section: Exercise Intolerance In Patients With Ventricular Preexcitationmentioning
confidence: 94%
“…It may vary from no symptoms at all to slight thoracic pressure or palpitations, or even syncope or sudden cardiac death as the first symptom. Currently, the idea of asymptomatic overt pre-excitation is challenged, as even in children, its presence is associated with reduced exercise capacity (due to APs-induced asynchrony and LV dysfunction) [49]. This might explain the increased risk for heart failure in adults with overt pre-excitation [50].…”
Section: Diagnosismentioning
confidence: 99%
“…In a compelling 2022 Europace article, Ksiazczyk et al . 56 identified that physical performance as measured by cardiopulmonary exercise testing (CPET) was worse in children with WPW even in the absence of symptoms or tachycardia. They found that key CPET parameters of physical performance were affected by pre-excitation.…”
Section: Wolff–parkinson–white Syndromementioning
confidence: 99%